1996
DOI: 10.1086/176874
|View full text |Cite
|
Sign up to set email alerts
|

The Radio Galaxy 3C 265 Contains a Hidden Quasar Nucleus

Abstract: We report the discovery of broad MgII emission from the high redshift radio galaxy 3C265 (z=0.81). We detect the broad line in the nuclear spectrum and in the spatially extended galaxian component, both near the nucleus and in the spectrum of an o -nuclear knot located 31 kpc south east of the nucleus of the galaxy. These data provide strong support for the simplest form of the uni cation hypothesis, that radio galaxies are quasars whose optical radiation is directed in the plane of the sky rather than into ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…The quantitative results of this analysis are presented in Table 5; also listed are the fluxes estimated using the intrinsic nuclear fluxes and extinctions listed in Table 4, accounting for the Galactic extinctions given in Table 6. The exclusion of 3C 265 from this analysis is not a great problem, because its predicted transmitted nuclear flux is several orders of magnitude fainter than the detection limit in the HST images, and spectropolarimetry (Dey & Spinrad 1996) suggests that any compact component is more likely to be light scattered close to the nucleus. The agreement between predicted and observed HST fluxes is generally very good, with the exception of the F555W flux of 3C 41, which is predicted to be much fainter than is observed.…”
Section: Comparison With Other Datamentioning
confidence: 99%
“…The quantitative results of this analysis are presented in Table 5; also listed are the fluxes estimated using the intrinsic nuclear fluxes and extinctions listed in Table 4, accounting for the Galactic extinctions given in Table 6. The exclusion of 3C 265 from this analysis is not a great problem, because its predicted transmitted nuclear flux is several orders of magnitude fainter than the detection limit in the HST images, and spectropolarimetry (Dey & Spinrad 1996) suggests that any compact component is more likely to be light scattered close to the nucleus. The agreement between predicted and observed HST fluxes is generally very good, with the exception of the F555W flux of 3C 41, which is predicted to be much fainter than is observed.…”
Section: Comparison With Other Datamentioning
confidence: 99%
“…At high z, mass estimates of radio galaxy hosts are rare. From an incomplete rotation curve, Dey et al (1996) derived a mass of 10 11 M for 3C 265 (z = 0.81). Using HST/NICMOS observations, Zirm et al (2003) confirmed that radio galaxy hosts are massive, even at high z. Stellar masses estimated by fitting stellar energy distributions (SEDs) to the NICMOS data are between 3 and 8 × 10 11 M .…”
Section: Introductionmentioning
confidence: 99%
“…If the compact quasar nucleus is hidden from our direct view, as is now known to be the case in some radio galaxies (e.g. Dey & Spinrad 1996), then in the context of the orientation-based unified schemes the radio-optical relation predicts that a high narrow-line luminosity L NLR is inescapable. The radio-optical relation is then an obvious candidate for the cause of the relation between narrow-line luminosity L NLR and L 408 for radio sources (Baum & Heckman 1989;Rawlings & Saunders 1991;McCarthy 1993;Rawlings 1993;Jackson & Rawlings 1997).…”
Section: The Optical Properties Of Radio Galaxiesmentioning
confidence: 94%
“…Antonucci 1993;Antonucci, Hurt & Kinney 1994;Dey & Spinrad 1996;Ogle et al 1997). However, the popular notion that the probability of obscuration is a strong function of the angle between the jet axis and the line of sight (e.g.…”
Section: Introductionmentioning
confidence: 99%